Numerical Study on the Fluid Forces of a Rigid Cylinder Covered by Helical Rods with Gap Due to the Variations of Incoming Flow Direction and Pitch at Reynolds Number 1000 - Syarifuddin, Arief; Prastianto, Rudi Walujo; Silvianita, Silvianita (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
Offshore structures such as a jacket platform, risers, conductors, mooring lines, Spars, and pipelines, are subject to severe vibration due to Vortex-induced vibration (VIV). This vibration can lead the structures to fatigue failure. One of a passive suppression device which effectively reduces the VIV is in the form of triple helical rods with gap covered to a cylinder. The present paper specially discusses the influence of incoming flow direction and pitch of helix on the induced fluid forces acting on the cylinder due to addition of helical rods at Reynolds number (Re) of 103. The configuration produced best reduction on drag and lift forces in CFD simulation are with 30D length of pitch for the incoming flow direction of 0° and 60°. Reduction on the drag and lift forces for incoming flow directions of 0° and 60° are respectively, 11.34% and 88.32%, and 10.99% and 97.94%.